1993
DOI: 10.1108/eb054404
|View full text |Cite
|
Sign up to set email alerts
|

The rules for managing cross‐functional reengineering teams

Abstract: The survival of many organizations depends on teams capable of engendering superior innovation in business processes. Successful teams always have two things in common. They are strongly committed to a shared purpose and specific performance goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 0 publications
1
109
0
4
Order By: Relevance
“…Sharing information and empathizing with employee concerns can help minimize resistance (Janson, 1993). Katzenbach and Smith (1993) propose that it is important for a BPR project team to have people from different interest groups. They identified that the size of a BPR project team, its members' level of skill, a shared goal, and mutual accountability among team members are important factors for successful project team management.…”
Section: Review Of Bpr Success Factorsmentioning
confidence: 99%
“…Sharing information and empathizing with employee concerns can help minimize resistance (Janson, 1993). Katzenbach and Smith (1993) propose that it is important for a BPR project team to have people from different interest groups. They identified that the size of a BPR project team, its members' level of skill, a shared goal, and mutual accountability among team members are important factors for successful project team management.…”
Section: Review Of Bpr Success Factorsmentioning
confidence: 99%
“…Another way to enhance the fit between marketing and manufacturing is the use of crossfunctional teams. As Katzenbach and Smith (1993) pointed out, companies who used cross-functional teams also identified common goals, shared objectives, and communication as being important. Thus, the fit between the functional departments will be more coherent and concrete.…”
Section: Discussionmentioning
confidence: 99%
“…They have documented one or many of the critical success factors listed in this paragraph: Leith, 1994; Feltes and Karuppan, 1995; Alavi and Yoo, 1995; Gorver et al, Johansson et al 1993, Barrett, 1994Towers, 1994;Furey, 1993;Dawe, 1996;Hagel, 1993;Zairi and Sinclair, 1995;Dixon et al, 1994;Harrisson and Pratt, 1993;Carr, 1994;Klein, 1994;Moad, 1993;Guha et al, 1993;Katzenbach and Smith, 1993;Talwar, 1993;Hammer, 1990;Bashein et al, 1994;Carr, 1993;Jackson, 1997;Guha et al, 1993;Grover et al, 1993;Bruss and Roos, 1993;Hagel, 1993;Guha et al, 1993;Feltes and Karuppan, 1995;Hammer and champy, 1993;Stow, 1993;hall et al, 1993;Zairi and Karuppan, 1995;Gould, 1993;Davenport, 1993;Towers, 1994;Rastogi, 1994;Klein, 1994;Clemmer, 1994;Shabana, 1996;Boyle, 1995. From the readings, critical success factors were extracted and grouped under five different categories: They have documented one or many of the critical success factors listed in this paragraph: Leith, 1994; Feltes and Karuppan, 1995; Alavi and Yoo, 1995; Gorver et al, Johansson et al 1993, Barrett, 1994Towers, 1994;…”
Section: Critical Success Factors From Litterature Reviewsmentioning
confidence: 99%